Nutrient-Enhanced Diet Reduces Noise-Induced Damage to the Inner Ear and Hearing Loss - Le Prell, C. G. (2011)
Oxidative stress has been broadly implicated as a cause of cell death and neural degeneration in multiple disease conditions; however, the evidence for successful intervention with dietary antioxidant manipulations has been mixed. In this study, we investigated the potential for protection of cells in the inner ear using a dietary supplement with multiple antioxidant components, selected for their potential interactive effectiveness. Protection against permanent threshold shift (PTS) was observed in CBA/J mice maintained on a diet supplemented with a combination of β-carotene, vitamins C and E, and magnesium when compared to PTS in control mice maintained on a nutritionally complete control diet. Although hair cell survival was not enhanced, noise-induced loss of Type II fibrocytes in the lateral wall was significantly reduced (p<0.05), and there was a trend towards less noise-induced loss in strial cell density in animals maintained on the supplemented diet. Taken together, our data suggest that pre-noise oral treatment with the high-nutrient diet can protect cells in the inner ear and reduce PTS in mice. Demonstration of functional and morphological preservation of cells in the inner ear with oral administration of this antioxidant supplemented diet supports the possibility of translation to human patients, and suggests an opportunity to evaluate antioxidant protection in mouse models of oxidative stress-related disease and pathology.